PEMILIHAN SAMPAH PADA SISWA DI SD MUHAMMADIYAH 3 KOTA PADANGSIDIMPUAN - Nasution, Nurul Hidayah; Siregar, Yuli Arisyah; Jufri, Soleman; Harahap, Dewani; Habibah, Nursalmah; Batubara, Adli Zil Ikrom; Mapilinda, Via Nesa; Harahap, Rosmawarni (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2025)
Schools are one of the sources of waste, both organic and inorganic. As a place where many people gather, schools can produce large amounts of waste, in addition to markets, households, industries, and offices. This community service aims to improve students' skills in sorting waste at school as part of environmental conservation efforts. This community service aims to improve students' skills in sorting waste at school as part of environmental conservation efforts. This activity uses a participatory model that involves school components such as teachers and elementary school students. The activity is carried out with elementary school students as the main target. There were 30 participants. This community service was carried out at SD Muhammadiyah 3 Kota Padangsidimpuan. This type of community service was health promotion by providing information on waste sorting. The methods used in this activity were lectures using PowerPoint and banners. The community service techniques used in this activity were health promotion, discussion, and question and answer sessions. The final result of this community service activity was that most students were able to understand the material presented on waste sorting. The community appeared to be orderly and followed the instructions given by the team during this activity. All participants stated that this community service activity was very useful because it increased students' knowledge on waste sorting. This community service activity was successfully implemented.